The Centennial of the West Ukrainian People’s Republic: the Aftertaste of the Jubilee (Major Trends in the Discourse on the History of the WUPR in Modern National Historiography) - Velykochyy, Volodymyr (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The article generalizes the findings about the history of the WUPR obtained by Ukrainian historiographers over the last decade of the 21st century, to outline major trends and methodological frameworks focusing on the ones which have hitherto received little attention for both subjective and objective reasons. It is stated that in Ukrainian historiography romantic positivism is the predominant methodological perspective on the history of the WUPR. Extensive research in this direction conducted mainly by experts in the so-called WUPR studies has yielded solid academic works such as An Encyclopedia of the WUPR in three volumes (the fourth volume is being prepared). It is stressed that the number and geographic diversity of researchers interested in exploring the history of the WUPR are expanding. In addition, there is an emphasis on qualitative changes in WUPR studies, which the author illustrates by analyzing the works of Ya. Hrytsak, O. Reient, О. Pavlyshyn, І. Monolatii written in the spirit of intellectual psychohistory, the history of everyday life.